Simulation Study of Direct-Shear Test on FRP-to-Concrete Bonded Joints by Means of XFEM - Jankowiak, Iwona (Engineering Transactions, 2026)
A proper numerical modelling of FRP-to-concrete bonded joints is crucial for determining their strength. In this paper, the results of numerical analyses performed using XFEM on such joints in direct-shear test are presented. The study uses a fracture mechanics approach based on the traction-separation law to define the FRP-concrete interface. It includes the definition of damage initiation as well as damage evolution, taking advantage of the fracture energy of plain concrete as well as the interfacial fracture energy of the analysed joint. The interfacial fracture energy of the bonded joint is essential for accurately describing the local bond–slip behaviour. The numerical study aims to investigate the sensitivity of direct-shear test models to the magnitude of fracture energies, material strengths, the type of adhesive, and the length of FRP-to-concrete joint. Some general results and conclusions of the performed analyses are presented.